Opis krivulj tečenja jekel z različnimi matematičnimi modeli - Arzenšek, Boris (Kovine zlitine tehnologije, 1998)
Steel deformation abilities are described by true stress - true strain (stress-strain) curves. Their exact knowledge is of a great importance at development of steel deformations technologies and construction of remaking devices. The stress - strain curves are established by tension, compression or torsion tests, mainly as possible by similar test like at projected deformation process. The course of stress - strain curves are often pictured by experimental results of by mathematical terms. The mathematical term, by which we wish to describe the deformation abilities of the steel, as exactly as possible, is chosen to get the minimum difference between experimental and functional results. In the paper the true stress - true strain curves for four different steels are represented. The curves were described by exponential and polynomial functions. In the work the differences between functional results and real deformations stresses were presented also. The deformation abilities of the choosen steels were made by compression tests. It is represented that not correct choosen function has a great influence on realistic presentation of the steel deformation abilities, specially at lower and higher deformation degrees.
Keywords: jeklo; mehanske lastnosti; deformacije; trdnost; matematični modeli